Physiological indexes, psychological resilience, sensory functions, and sleep quality on the cognitive function of older adults with pre-frailty: a predictive study - Lu-Ling Hsieh; Shu-Fang Chang; Hsiao-Chi Tsai (Journal of Men's Health, 2023)
Population ageing has increased the prevalence of prefrailty comorbid with cognitive impairment among older adults. However, few studies have explored the risk factors common to both prefrailty and cognitive impairment. This study determined the predictive accuracy of demographic characteristics, physiological indexes, psychological resilience, sensory function, and sleep quality on the cognitive function of older adults with prefrailty. In this cross-sectional study, the physiological indexes, psychological resilience, sensory function, sleep quality, and cognitive function of 167 community-dwelling older adults with prefrailty recruited through purposive sampling were measured. SPSS software was used for data coding and compilation. Data analysis involved the use of descriptive statistics, the independent samples t test, the chi-square test, and logistic regression. Overall, in cognitive function, there was no difference in gender but were in age, were incapable of text messaging, had a greater number of chronic diseases, were less able to perform activities of daily living, had low psychological resilience, and had depressive tendencies. In addition, Text messaging capability and depression status can all predict the cognitive impairment state of prefrail older elderly. Physiological indexes, psychological resilience, sensory function, and sleep quality can affect cognitive function in older adults with prefrailty. Meanwhile, depressive tendencies and the inability to send text messages on a mobile device constituted critical predictors of cognitive function in the participants.